An insight into using DFT data for Calphad modeling of solid phases in the third generation of Calphad databases, a case study for Al. (June 2019) - Bigdeli, Sedigheh; Zhu, Li-Fang; Glensk, Albert; Grabowski, Blazej; Lindahl, Bonnie; Hickel, Tilmann; Selleby, Malin
Abstract: In developing the next generation of Calphad databases, new models are used in which each term contributing to the Gibbs energy has a physical meaning. To continue the development, finite temperature density-functional-theory (DFT) results are used in the present work to discuss and suggest the most applicable and physically based model for Calphad assessments of solid phases above the melting point (the breakpoint for modeling the solid phase in previous assessments). These results are applied to investigate the properties of a solid in the superheated temperature region and to replace the melting temperature as the breakpoint with a more physically based temperature, i.e., where the superheated solid collapses into the liquid. The advantages and limitations of such an approach are presented in terms of a new assessment for unary aluminum.